Three-dimensional modeling and numerical analysis of fractional flow reserve in human coronary arteries - Dai, Neng; Lv, Hui-Jie; Xiang, Ya-Fei; Fan, Bing; Li, Wei-Ming; Xu, Ya-Wei (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Noninvasive fractional flow reserve (FFR) computed from CT (FFR CT ) is a novel method for determining the physiologic significance of coronary artery disease (CAD). Several clinical trials have been conducted, but its diagnostic performance varied among different trials. Aim : To determine the cut-off value of FFR CT and its correlation with the gold standard used to diagnose CAD in clinical practice. Material and methods : Forty patients with single vessel disease were included in our study. Computed tomography scan and coronary angiography with FFR were conducted for these patients. Three-dimensional geometric reconstruction and numerical analysis based on the computed tomographic angiogram (CTA) of coronary arteries were applied to obtain the values of FFR CT . The correlation between FFR CT and the gold standard used in clinical practice was tested. Results : For FFR CT , the best cut-off value was 0.76, with the sensitivity, specificity, positive predictive value and negative predictive values of 84.6%, 92.9%, 88% and 73.3%, respectively. The area under the receiver-operator characteristics curve was 0.945 (p < 0.0001). There was a good correlation of FFR CT values with FFR values (r = 0.94, p < 0.0001), with a slight overestimation of FFR CT as compared with measured FFR (mean difference 0.01 ±0.11, p < 0.05). For inter-observer agreement, the mean κ value was 0.69 (0.61 to 0.78) and for intra-observer agreement the mean κ value was 0.61 (0.50 to 0.72). Conclusions : FFR CT derived from CT of the coronary artery is a reliable non-invasive way providing reliable functional information of coronary artery stenosis.